2016
DOI: 10.5001/omj.2016.27
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of IOS Device-based uHear as a Screening Tool for Hearing Loss: A Preliminary Study From the Middle East

Abstract: uHear in any setting lacks specificity in the range of normal hearing and is highly unreliable in giving the exact hearing threshold in clinical settings. However, there is a potential for the use of uHear if it is used to rule out moderate hearing loss, even in a clinical setting, as exemplified by our study. This method needs standardization through further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
1
9
0
3
Order By: Relevance
“…Al‐Abri et al ( n = 70) reported that uHear was inconsistent even in a soundproof audiometric booth and lacked specificity in the range of normal hearing. 12 These results align with our findings; in addition to recording a moderate specificity of 78%, we found that when patients were stratified by level of hearing impairment, uHear significantly overestimated hearing impairment in those with normal hearing. Livshitz et al ( n = 60) determined that uHear did not accurately assess hearing thresholds, specifically in the elderly population.…”
Section: Discussionsupporting
confidence: 91%
“…Al‐Abri et al ( n = 70) reported that uHear was inconsistent even in a soundproof audiometric booth and lacked specificity in the range of normal hearing. 12 These results align with our findings; in addition to recording a moderate specificity of 78%, we found that when patients were stratified by level of hearing impairment, uHear significantly overestimated hearing impairment in those with normal hearing. Livshitz et al ( n = 60) determined that uHear did not accurately assess hearing thresholds, specifically in the elderly population.…”
Section: Discussionsupporting
confidence: 91%
“…Audiometric tests can be conducted on specialized equipment as well as on generally accessible electronic devices such as personal computers [ 10 , 22 , 23 ] or mobile devices [ 4 - 9 , 15 - 21 , 24 , 25 ]. However, reliable results may only be obtained if they are correctly calibrated and conducted in silence [ 1 , 15 , 21 , 26 , 27 ]. Assuming that mobile devices sold with bundled headphones have similar frequency characteristics of the sound system within the devices of the same model, it is possible to share calibration coefficients within these groups.…”
Section: Introductionmentioning
confidence: 99%
“…11 A study showed that its specificity improved to 90% when the application was used in a soundproof booth but decreased in a typical hearing environment. 12 These findings were replicated in many studies. 13 , 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 75%